2022
DOI: 10.3390/ijms232113172
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Approach to Discover Tuberosin as a Potent Activator of Pyruvate Kinase M2, Targeting Cancer Therapy

Abstract: Metabolic reprogramming is a key attribute of cancer progression. An altered expression of pyruvate kinase M2 (PKM2), a phosphotyrosine-binding protein is observed in many human cancers. PKM2 plays a vital role in metabolic reprogramming, transcription and cell cycle progression and thus is deliberated as an attractive target in anticancer drug development. The expression of PKM2 is essential for aerobic glycolysis and cell proliferation, especially in cancer cells, facilitating selective targeting of PKM2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…This might be due to the fact that compounds present in essential oil are mostly volatile constituents, whereas that in extracts are usually non-volatile compounds. It is imperative to carry out pharmacokinetic parameter screening of herbal medicine to obtain active constituents [ 37 ]. After screening compounds for drug-likeness (Lipinski's rule) and bioavailability score (Abbott), 52 active compounds were retrieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to the fact that compounds present in essential oil are mostly volatile constituents, whereas that in extracts are usually non-volatile compounds. It is imperative to carry out pharmacokinetic parameter screening of herbal medicine to obtain active constituents [ 37 ]. After screening compounds for drug-likeness (Lipinski's rule) and bioavailability score (Abbott), 52 active compounds were retrieved.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular docking score indicated that the significant node (benzyl benzoate), which had a high degree obtained from network analysis, had the strongest affinity with probable target genes. Additionally, according to prior studies, benzyl benzoate substantially reduces inflammation of the skin [ 37 ]. This finding suggests that one or more compounds may interact with many target proteins instead of just one molecule and one target protein.…”
Section: Discussionmentioning
confidence: 99%
“…Computational methods such as molecular dynamics (MDs) are used to understand how ligands behave in the binding pocket of receptors based on their time-dependent conformational stability. Several studies have demonstrated its practical application in identifying new inhibitors in a number of applications [ 33 , 34 , 35 , 36 ]. In this study, MD analyses were performed with Gromacs version 2019.4 [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are four different isoforms of PK: PKL, PKR, PKM1, and PKM2, which determine the rate of glycolysis [ 11 , 12 ]. Among them, pyruvate kinase M2 (PKM2) plays an important role in cell proliferation and is mainly expressed in the regenerated region of damaged tissues [ 10 , 13 ]. In addition, PKM2 promotes angiogenesis by facilitating endothelial cell migration and extracellular matrix (ECM) attachment [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%